Childhood meningitis in Kuwait in the era of post pneumococcal conjugate vaccination: A multicenter study. Issue 6 (November 2017) - Sadeq, Hussain; Husain, Entesar H.; Alkoot, Amna; Atyani, Suha; Al-fraij, Abdullah; Al-Daithan, Abdulrahman; AlSaleem, Talal; Taher, Anfal; Alenezi, May
Abstract: This is a retrospective study to evaluate epidemiology and etiologies of childhood meningitis in Kuwait after the routine introduction of the pneumococcal conjugate vaccine. The data was collected from 196 patients in the period of 2010–2014. Aseptic meningitis accounted for 51% of the cases, bacterial meningitis accounted for 29% cases and partially treated meningitis were 20%. Organisms causing bacterial meningitis were: Streptococcus pneumoniae 40.4%, Neisseria meningitidis 17 .6%, Haemophilus spp. 12.2%, other gram positive or negative 19.3%, and Group B Streptococcus 8.8%. The hospitalization was complicated by admission to the ICU in 16.3% patients. Sequelae on discharge were seen in 4%, and 2.5% died of complications of meningitis. In children with pneumococcal meningitis, 48% were admitted to the ICU, 35% were discharged with sequelae and 13% died. In the era of post pneumococcal conjugate vaccination, S. pneumoniae remains the leading cause of bacterial meningitis with the greatest morbidity and mortality.